Scientific Oriented E-Book Development On Natural Science Lesson Of Grade V Elementary School - Kusumayuni, Putu Netha; Agung, Anak Agung Gede (Jurnal Ilmiah Sekolah Dasar, 2021)
The research was conducted based on the results of an analysis of the need for learning media in elementary schools during the online learning process where less innovative learning media and the application of conventional methods have an impact on students' interest and understanding of science lesson content. The purpose of this study is to describe the design process and know the results of E-Book validation according to the results of expert reviews, individual tests, and small group tests of scientifically designed E-Book products. The products developed are expected to be utilized independently by students. This research is a development research using addie development model. The method of data collection in this study is questionnaire with quantitative descriptive analysis techniques. This research is limited to the development stage, as it is not possible to involve many students during the Covid-19 pandemic. Media validation based on expert assessment of lesson content content obtained a score of 91.67% with excellent qualifications, instructional design experts with a score of 100% with excellent qualifications, learning media experts obtained a score of 100% with excellent qualifications. User test results through individual tests on 3 students scored 93.33% with excellent qualifications, and user tests through small group tests on 12 students scored 95.00% with excellent qualifications. Based on the analysis of data from the validation results obtained, it can be concluded that this scientifically designed E-Book media is eligible to be used as a learning medium on science lesson content in grade V elementary school. The implications of the development of this scientific-based E-book requires supporting facilities for the operation of E-Book both laptops and mobile phones and supported by the ability to operate it, so that it can be used independently